The expression x^2 - x represents a quadratic equation in standard form. It is a polynomial of degree 2, with x raised to the power of 2 and a coefficient of -1 for the linear term. This expression can be factored as x(x-1), which shows that it has two factors, x and (x-1). It is a parabolic function that opens upwards and crosses the x-axis at x=0 and x=1.
Chat with our AI personalities
The answer would be 3x if 'X2' is '2x', but if 'X2' is x2, then the total answer would be x2 + x.
x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)
x4 +x2 =x2 (x2+1)
If 'x' is more than 1, then x2 is more than 'x'. If 'x' is less than 1, then x2 is less than 'x'.
-167